Current Epidemiology of Revision Total Knee Arthroplasty in the United States - Delanois, Ronald E.; Mistry, Jaydev B.; Gwam, Chukwuweike U.; Mohamed, Nequesha S.; Choksi, Ujval S.; Mont, Michael A. (The Journal of arthroplasty, 2017)
Revision surgery for failed total knee arthroplasty (TKA) continues to pose a substantial burden for the United States healthcare system. The predominant etiology of TKA failure has changed over time and may vary between studies. This report aims to update the current literature on this topic by using a large national database. Specifically, we analyzed: (1) etiologies for revision TKA; (2) frequencies of revision TKA procedures; (3) various demographics including payer type and region; and (4) the length of stay (LOS) and total charges based on type of revision TKA procedure. The Healthcare Cost and Utilization Project (HCUP) National Inpatient Sample (NIS) database was used to identify all revision TKA procedures performed between 2009 and 2013. Clinical, economic, and demographic data were collected and analyzed for 337,597 procedures. Patients were stratified according to etiology of failure, age, sex, race, US census region, and primary payor class. The mean LOS and total charges were also calculated. Infection was the most common etiology for revision TKA (20.4%), closely followed by mechanical loosening (20.3%). The most common revision TKA procedure performed was all component revision (31.3%). Medicare was the primary payor for the greatest proportion of revisions (57.7%). The South census region performed the most revision TKAs (33.2%). The overall mean LOS was 4.5 days, with arthrotomy for removal of prosthesis without replacement procedures accounting for the longest stays (7.8 days). The mean total charge for revision TKAs was $75,028.07. Without appropriate measures in place, the burden of revision TKAs may become overwhelming and pose a strain on providers and institutions. Continued insight into the etiology and epidemiology of revision TKAs may be the principle step towards improving outcomes and mitigating the need for future revisions.